Impact of COVID-19 pandemic on women reproductive health and family planning services - Taywade, Manish; Pradhan, Rudra Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Globally, women and adolescents health in the reproductive age group are heavily affected during the ongoing coronavirus disease - 2010 (COVID-19) pandemic. Contraception shortage across the world. Sustainable development goal, target 3.7 is “to ensure universal access to sexual and reproductive healthcare services, including for family planning, information and education and integration of reproductive health into national strategies and programmes.” The demand of health workers and supply chain are affected and impacted the availability and accessibility to the sexual and reproductive health